Health status of the female inside the probation home, Namkum, Ranchi - Kiran, Kumari Asha; Kumari, Anju Prabha; Hashmi, Syed Ajaz; Kumar, Satish; Kumari, Gunjan; Kashyap, Vivek (International Journal Of Community Medicine And Public Health, 2021)
Background: This study was intended to have a close look at the need of women in probation home and their health related aspects. The objective of the study was to obtain the socio-demographic profile of the inmates of probation home and to assess the health status of the study population. Methods: This was an institutional based cross sectional study which was carried out among the inmates residing in the probation home, Namkum, Ranchi. Data was collected using pretested semi-structured questionnaire on 14 January 2020 during a health camp. The questionnaire was designed to collect information on socio-demographic profile, health detail like co-morbid conditions, presenting complaint and findings of general examination. Data collected was entered in microsoft excel sheet and was analyzed using SPSS software version 20. Results: Out of total 54 inmates residing there, only 44 females willing to participate in the study were enrolled in the study, the response rate was 81.48%. More than two third (81.8%) population were of age group 15-25 years of age. Less than a half (45.5%) population had no formal education. On general examination we found that 75% were having mild to moderate pallor and 11.36% participants were underweight. More over the presenting complaint was also supportive that is weakness in 18.18% of participants. Conclusions: Based on our result we concluded that the population residing in the probation home was vulnerable to malnutrition and if not corrected may become susceptible to communicable and non-communicable diseases.